MODERNISASI PENDIDIKAN ISLAM: UPAYA MERELEVANSIKAN NILAI-NILAI ISLAM DENGAN TANTANGAN MODERNITAS - Mandala, Gerry; Nursikin, Mukh (As-Sulthan Journal of Education, 2025)
The modernization of Islamic education is an inevitable necessity in responding to the dynamics of contemporary civilization characterized by the advancement of science, technology, and socio-political transformation. This article aims to analyze the concept of Islamic education modernization as an effort to relate Islamic values to the challenges of modernity while preserving the essence of Islamic spirituality and morality. Using a descriptive-qualitative approach and literature analysis from various scholarly sources on contemporary Islamic education, the study reveals that modernization involves curriculum reconstruction, integration between religious and general sciences, and the utilization of digital technology in learning. Socio-political dynamics play a significant role in shaping educational policies, while key challenges include the dichotomy of knowledge, inequality of educational facilities, and limited teacher competence in pedagogical innovation. Nevertheless, the future prospects of Islamic education remain promising if modernization is directed toward developing a progressive, humanistic, and value-based educational system. Thus, modernization should not be equated with westernization but understood as a continuous renewal process to meet modern challenges while maintaining Islamic identity.